Synthesis, Crystal Structure and Antiproliferative Activity of Mn(II) Complexes of Demethylcantharate - Wang, Yun-Yun; Hu, Rui-Ding; Lin, Qiu-Yue; Zhao, Yu-Ling; Wang, Na (Asian Journal of Chemistry, 2010)
A complex with the molecular formula [Mn(C 8H8O5)(H2O)2] formed by Mn(II) with demethylcantharate (DCA = 7-oxa-bicyclo[2.2.1]heptane-2,3-bicarboxylate, C8H8O5) was characterized by elemental analysis, IR and single crystal X-ray diffraction. The complex was crystallized in the orthorhombic crystal system and Iba2 space group with a = 1.89914(5) nm, b = 1.03558(2) nm, c = 1.04856(2) nm; a = 90°, b = 90°, g = 90°, V = 2.06221(8) nm3, Dc = 1.772 g/cm3, Z = 8, F(000) = 1128, R = 0.0361, wR = 0.0981 [I > 2s(I)]. The antiproliferative activity test indicates that the complex has a higher inhibitive effect on human hepatoma cells SMMC7721 (IC50 = 38.0 ± 0.9 μmol L-1). The inhibition rates of the complex are much higher than those of demethylcantharidin (NCTD)